Упростите выражение:
(5m−9)(−9n−2)+(−6m+6)(−6n+4)
(3a+5b)(6a+5b)+(−7a−8b)(−5a−8b)
(−4c−3)(2c+3)−(5c−9)(−9c−2)
(6c+6)(3c−3)−(6c−4)(c−8)
4x(6x−7)(−8x^2+8)
(−5x−3y)(−8x+1)−(−8x−2y)(−3x+9)
−1x(5x−4)(5x^2+7)
(−5a−4b)(7a−4b)+(−4a−3b)(2a+3b)
(7m−8)(−n+1)+(−7m+9)(−9n−7)
−8x^2(5x+8)(6x^2+5)
−1c^2(9c−4)(c−5)
3a^2(−5a^2−3)(5a^2−3)
−6x^3(−2x+8)(−9x^2+9)
(−a+9b)(5a+b)+(6a+6b)(3a−3b)
−2c(−9c−2)(−7c−9)
−5c(5c+3)(c+7)
Answers & Comments
а)(5m-9)(-9n-2)+(-6m+6)(-6n+4)=-45mn+18+36mn+24=-9mn+42
б) (3a+5b)(6a+5b)+(-7a-8b)(-5a-8b)=18a^2+25b^2+30ab+25b^2+35a^2+64b^a=53a^2+30ab+114b^2
в) (-4c-3)(2c+3)-(5c-9)(-9c-2)=-8c^2-12c-6c-9-(-45c^2)-10c+45c+18=-53c^2-6c-9+55c=9+53c^2-49c
г) (6с+6)(3с-3)-(6с-4)(с-8)=18с-18+18с-18-6с^2-48c-4c+32=36c-44c-6c^2-48c=-56c-6c^2
d) 4x(6x-7)(-8x^2+8)=(24x^2-28x)(-8x^2+8)=-192x^4+192x^2+224x^3-224x
теперь сам и решай